PERTIMBANGAN ASPEK MITRA TUTUR DALAM PERILAKU BERTUTUR ANAK DI TK KARTIKA II-27 BANDARLAMPUNG TAHUN AJARAN 2012/2013 DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA DI TK - Heny Hartawati; mulyanto widodo; eka sofia agustina (FKIP Universitas Lampung, 2013)
The problems in this research are the consideration of speech partner aspect of children’s speech berhavior in kindergarten Kartika II-27 Bandarlampung in school year 2012/2013 and its implications for learning Indonesian in kindergarten. The purpose of this research are to describe the consideration of speech partner aspects of children’s speech berhavior in kindergarten Kartika II-27 Bandarlampung in school year 2012/2013 and its implications for learning Indonesian in kindergarten. The research design was descriptive qualitative. The data of this research were students speech of class A in kindergarten Kartika II-27 Bandarlampung.The results of this study showed that the children’s speech behavior based on the consideration the aspects can be evaluated in terms of social distance and social status hearer. The child’s behavior based on social distance tells the hearer and the social status of the hearer consists told the hearer behavior very close to the high status, very close to equal status, very close to the low status, quite close to the high status, quite close to equal status, quite close to the low status, quite far to the high status, quite far to equal status, quite far to the low status, considerable far with high status, considerable far with equal status, considerable far with low status. The data was the speech of direct and indirect acts. Direct acts consist of data obtained on (1) speech acts in the target, and (2) direct speech acts arguing. Indirect acts of the data obtained consists of (1) indirect speech acts in question mode, (2) indirect speech acts mode of engagement with other people, (3) indirect speech is not the mode of stating the facts, (4) indirect speech acts to complain mode, (5) indirect speech acts with praise mode, (6) indirect speech acts with reigning mode.The results are expected to be an information that can be used as an alternative for the teachers to evaluate the students ability to communicate. When associated with kindergarten learning varied instructional strategies are used to full fill the indicator “Telling a simple event experience to the teachers and friends in the class” as defined in the syllabus. Key words : speech acts, partner aspect, social distance, social status